Anisotropy of the Mechanical Properties of Twin-roll Cast, Rolled and Heat-treated AZ31 as a Function of Temperature and Strain rate. (2015) - Berge, F.; Krüger, L.; Ullmann, M.; Krbetschek, C.; Kawalla, R.
Abstract: The influence of temperature on the mechanical properties of twin-roll cast, rolled and heat-treated AZ31 was investigated under tensile loading from different directions (0°, 90). Therefore, quasi-static tensile tests with a strain rate of 0.76×10 −3 s −1, 0.73×10 −2 s −1, and 0.72×10 −1 s −1 were performed with an electromechanical universal testing device in the temperature range of −20 °C to 300 °C. The initial material exhibits a recrystallized microstructure with an average grain size of 7 μm. With increasing temperature and decreasing strain rate, the flow stress decreases and the elongation increases. Rising strain rates and decreasing temperatures enlarge the difference in stress between the deformation directions of 0° and 90°. Below 200 °C, the difference in elongation (0°−90°) remains at almost the same absolute level of 6 % (10 −3 s −1 ) and 4 % (10 −1 s −1 ). Above 200 °C, this difference increases, whereby an increase in the strain rate tends towards a reduction in the difference in elongation.